Pengaruh Keahlian Audit, Tekanan Ketaatan, Kompleksitas Tugas, Dan Pengalaman Terhadap Audit Judgment (Studi Empiris pada Kantor Akuntan Publik di Surakarta dan Yogyakarta) - Kelana Nila Sari, Erika, Drs. Wahyono, M.A., Akt.C.A (2017)
This research has a purpose and that is to know the influence of the skill audit, the pressure of obedience, the complexity of the tasks, and experience of the audit judgement. The population in this research is the auditor who worked in the Office of Public Accountant in Surakarta and Yogyakarta. Sample collection method by using the technique of sampling convience. The samples used in the study totalled 46 respondents. In this study to analyze the data using multiple regression analysis. T test results indicate that audit expertise and experience to audit judgement. While the pressure of obedience and the complexity of the task has no effect against the audit judgement. Research results show that R2 values obtained 0.458 45.8% which means that the audit judgement is influenced by the expertise of the audit, the pressure of obedience, the complexity of the tasks, and experience. Rest as much as 54.2% influenced by variables outside of the model. Keywords: audit skills, the pressure of obedience, the complexity of the task, experience, and judgment of the audit.